On convergence almost everywhere of multiple fourier integrals - Anvarjon Ahmedov,; Norashikin Abdul Aziz,; Mohd Noriznan Mohtar, (Penerbit Universiti Kebangsaan Malaysia, 2011)
of the polyharmonic operator, which coincides with the multiple Fourier integrals summed over the domains corresponding to the surface levels of the polyharmonic polynomials. It is proved that the partial sums of the multiple Fourier integrals of a function 2 f ∈ L (RN ) converge to zero almost-everywhere on RN \ supp f .